“Secure Lane”: Exploring DOTA 2 Players’ Experience on Their Accidental Vocabulary Learning - Rachmad, Arvega; Adi, Sugeng Susilo; Ratri, Devinta Puspita (IJIE (Indonesian Journal of Informatics Education), 2022)
Vocabulary is the key of language where people need to process words to understand their meaning of words. Learning vocabulary is not merely can be obtained from classroom interaction. It can be done outside classroom with the aid of various media, one of which is video games developed in English. Learning English from activities outside the classroom like playing video games can gain incidental vocabulary which has relation with repetition of the interaction from the learner with target language which is English. DoTA 2 is a popular video game among students since it not only provides a pleasurable experience for players but also allows them to engage with one another via the use of English. This survey study aimed at figure out the relation between player intensity of playing DoTA 2 and their vocabulary size. The data was gained from 100 students of a state university in Indonesia who played Dota 2 by distributing a questionnaire adopted from Cabraja (2016) to get the players’ view and Schmitt’s Vocabulary Levels Test (VLT) to know players’ vocabulary level. The findings showed that participants who plays DoTA 2 more regularly got a higher score on the Vocabulary Level Test score than participants who played Dota 2 less regularly. According to their experience, participants with higher score feel more confident when communicate with other player using English. It shows that playing the video game, DoTA 2 in this case, contributes a significant impact on players'/students' accidental vocabulary acquisition as well as giving a less daunting experience when learning English.